Hollywood and History: What the Movies Get Wrong from the Ancient Greeks to Vietnam - Duducu, Jem (Rowman & Littlefield Publishers, 2023)
There is no shortage of Hollywood films about historical events, but what do the movies actually get right, and why do they get so much wrong? Hollywood loves a story: good guys versus bad guys, heroes winning the day, and the guy gets the girl. But we all know real life isn’t exactly like that, and this is even more true when we look at history. Rarely do the just prevail and the three-act story cannot exist over continents and decades of human interaction. So, when Hollywood decides to exploit history for profit, we end up with a wide array of films. Some are comedies like Monty Python and the Holy Grail, others are little more than action films playing dress up like Gladiator, and many are Oscar contenders burdened with an enormous sense of self-importance. But very few are historically accurate. From Cleopatra to Da 5 Bloods, the reality is no matter what Hollywood’s intentions are, almost all historical films are an exaggeration or distortion of what really happened. Sometimes the alterations are for the sake of brevity, as watching a movie in real time about the Hundred Years War would literally kill you. Other additions may be out of necessity, since nobody thought to write down the everyday conversations between King Henry VIII and his second wife, Anne Boleyn, for The Other Boleyn Girl. And some projects twist the facts to suit a more sinister purpose. In Hollywood and History, Jem Duducu takes readers through thousands of years of global history as immortalized and ultimately fictionalized by Hollywood, exploring many facets of the representation of history in movies from the medieval times to the wild west and both World Wars. Along the way, readers will also better understand Hollywood’s own history, as it evolved from black and white silent shorts to the multiplex CGI epics of today. As studios and audiences have matured through the years, so too have their representations of history. Armies will clash, leaders will be slain, empires will fall, and a few historical inaccuracies will be pointed out along the way. A must-read for film and history fans alike.